2003
DOI: 10.1038/sj.onc.1206181
|View full text |Cite
|
Sign up to set email alerts
|

Role for RhoB and PRK in the suppression of epithelial cell transformation by farnesyltransferase inhibitors

Abstract: Recent genetic investigations have established that RhoB gain-of-function is sufficient to mediate the antitransforming effects of farnesyltransferase inhibitors (FTIs) in H-Ras-transformed fibroblast systems. In this study, we addressed the breadth and mechanism of RhoB action in epithelial cells transformed by oncoproteins which are themselves insensitive to FTI inactivation. Rat intestinal epithelial (RIE) cells transformed by activated K-Ras or Rac1 were highly sensitive to FTI-induced actin reorganization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 41 publications
(65 reference statements)
0
51
1
Order By: Relevance
“…51 for a recent review). It is possible that the pathways leading to cytoskeletal versus gene regulation diverge at the very beginning of the isoprenylation step and that different members of the Rho family initiate different cascades (52)(53)(54)(55)(56)(57)(58)(59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%
“…51 for a recent review). It is possible that the pathways leading to cytoskeletal versus gene regulation diverge at the very beginning of the isoprenylation step and that different members of the Rho family initiate different cascades (52)(53)(54)(55)(56)(57)(58)(59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%
“…Generation of recombinant retroviruses has been described previously that a hemagglutinin antigen epitope (HA)-tagged RhoB-WT cDNA or RhoB-GG cDNA was subcloned into the replication-incompetent retroviral vector MSCVpac, which includes a puromycin selection marker (Zeng et al, 2003). Recombinant MSCVpac viruses were packaged by standard methods in Phoenix cells.…”
Section: Virus Production and Infectionmentioning
confidence: 99%
“…It has been shown that oligodendrocyte lineage transcription factor 2 inhibits the motility of a certain human glial tumor cell line by activating RhoA (22). This may explain the selective antitumor activity of farnesyl transferase inhibitors, which, although originally designed to attenuate the action of Ras proteins, are now believed to act including in glioblastoma multiforme cells at least in part by activating Rho (40)(41)(42). Conversely, metastatic tumors whose cells invade using a rounded, amoeboid movement are clearly susceptible to Rho inhibition (39).…”
Section: Molecular Cancer Therapeuticsmentioning
confidence: 99%
“…Once in the cytosol, the cell-penetrating moiety is released, thereby allowing C3 transferase to freely diffuse intracellularly and inactive RhoA, RhoB, and RhoC but not related GTPases such as Cdc42 or Rac1. C3 transferase inhibits Rho proteins by ADP ribosylation on Asn 41 in the effector binding domain of the GTPase. Cells were then lysed and RhoA activity was measured by the RhoA G-LISA Activation Assay (TebuBio) or alternatively cells were stained for F-actin.…”
Section: Rho Activation Assay and C3 Exoenzyme Inhibition Assaymentioning
confidence: 99%